Polish validation of the Transplant Effects Questionnaire - Dębska, Grażyna; Milaniak, Irena; Dębska-Ślizień, Alicja; Gołkowski, Filip (Frontiers in Psychiatry, 2023)
The Transplant Effects Questionnaire (TxEQ) assesses specific recipients' reactions to receiving a transplanted organ, including worry about the transplant, Guilt regarding the donor, disclosure of having undergone transplantation, adherence to medical treatment, and responsibility to the donor, family, or medical staff. Poland has no standardized tool for evaluating the emotional reaction to transplantation. The study aimed to assess the basic psychometric properties, such as the reliability and validity of the Polish translation of TxEQ-PL. Material and methods: The study involved 84 patients after kidney transplantation. The average age of the subjects was 49.87 years (±15.27). The study used the diagnostic survey method, the Polish versions of the Revised Life Orientation Test (LOTR-R), the Mental Component Summary of the SF-36 (SF-36-MCS), and the Hospital Anxiety and Depression Scale (HADS). The Confirmatory Factor Analysis (CFA) was used to verify the factor structure of TxEQ -P.L. variables. Results: The TxEQ-PL version has satisfactory internal consistency for each subscale (Cronbach's alpha> 0.7). The analysis showed a significant negative relationship between optimism (LOT-R) and the TxEQ-PL subscales: worry about transplant and disclosure of having undergone transplantation and a positive relationship in the subscale of adherence to medical treatment. In addition, a significant negative relationship was found between the subscale: adherence to medical treatment and the severity of depression and intensity of anxiety (HADS); also, a positive relationship with the Mental Component Summary of the SF-36 (SF-36-MCS). The intensity of anxiety and severity of depression were positively related to the TxEQ-PL subscale of disclosure of having undergone transplantation and negatively associated with the Mental Component Summary of the SF-36 (SF-36-MCS). The Confirmatory Factor Analysis confirmed the five-factor structure of the TXEQ-PL questionnaire (RMSEA=0.083). Not the best fit is indicated by the value of comparative fit indexCFI=0.813 and SRMR = 0.10. The result of the chi-squared test (220) = 340 was statistically significant; p < 0.001. Conclusions: TxEQ-PL is useful for assessing emotional reactions to organ transplantation. The tool has a factor structure identical to the original English version and comparable psychometric properties.